PENGEMBANGAN SISTEM INFORMASI AKAD MUDHÄRABAH BANK SYARIAH BERBASIS DSS DENGAN MENGGUNAKAN METODE AHP - Hartono, Setyo Budi; Susatyono, Jarot Dian; Kholiq, Abdul (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2016)
This research aims to develop a scoring system awarding financial cooperation that existed at Syariah Banking using various contract in it. The development of this system will replace the performance of the analytical assess and decide on the granting of the contract to mudhÄrib. With this system will streamline the performance of the analysis in maximizing profits at BMT. Given the increased profitability for the results to be obtained by sahib al-mal will also increase. The methodology in this research is to analyze the process towards a needs assessment, process analysis and counting processes are the priorities of the system. This study resulted in a system that will be applied in analyzing the Mudharabah where deemed profitable or have a larger revenue share.